IMPLEMENTATION OF NORTH WEST CORNER METHOD AND MODIFIED DISTRIBUTION METHOD IN OPTIMIZING FISH DISTRIBUTION COSTS USING MATLAB PROGRAM - Sitanggang, Eby Agusriani; Ahyaningsih, Faiz (UIN Sumatera Utara, 2022)
Calculating distribution costs using the transportation method seeks to solve the problem of goods sent from source to destination so that the most optimal amount of transportation costs will be obtained to maximize profits. CV. Horizon Sibolga Group is a company that provides raw fish for sale to fish processing consumers. The company is located at Gatot Subroto street Number. 108 Pondok Batu Sarudik, Central Tapanuli Regency, North Sumatra Province. In this study, the North West Corner method will be used to find an initial feasible solution, and the Modified Distribution method will be used as an optimization test. If the test results show an optimal solution, then the allocation has been optimal and can be said to have reached the most profitable value. These results were obtained using Matlab software. Before the calculation, the company incurs distribution costs for a year of Rp. 963,000,000. From the research results, the total cost obtained after using the North West Corner method as an initial feasible solution is Rp. 928,831,000, and after using the Modified Distribution method as an optimization test, the total distribution cost is Rp. 923,058,000. So that the method used can save costs of Rp. 39,942,000, with a percentage of 4.14%.Keywords: Optimization, Transportation Problems, North West Corner, Modified Distribution, Matlab.